All shallow coastal habitats matter as nurseries for Mediterranean juvenile fish - Adrien Cheminée (Nature Portfolio, 2021)
Abstract Coastal zones are ecosystems of high economic value but exposed to numerous disturbances, while they represent nurseries for many fish species, raising the issue of the preservation of their functions and services. In this context, the juvenile fish assemblages of all types of habitats present in shallow coastal zones were studied on the south-east coast of France using underwater visual censuses in warm (June–July 2014) and cold (April 2015) periods. A total of fourteen habitat types were characterized, which could be grouped into three broad categories, rocky substrates (natural and artificial), sedimentary bottoms with all levels of granulometry, and seagrass beds including Cymodocea nodosa and Posidonia oceanica meadows; the ecotones or interfaces between the three broad habitat categories were individualized as particular habitat types. The abiotic and biotic descriptors of the 14 habitat types individualized did not vary with time, except for a higher cover percentage and canopy height of macrophytes in the warm period, which increased the three-dimensional structure of some habitats. The taxonomic composition and density of juvenile fish assemblages were analyzed using both multivariate and univariate descriptors, after grouping the 57 fish species recorded into 41 well-individualized taxa. Juvenile fishes were recorded in all habitat types, with higher mean species richness and abundance during the warm than the cold period. The richest habitats in terms of both fish species richness and abundance were the natural rocky substrates and the interfaces between Posidonia beds and the other habitats. Although juvenile fish assemblage composition differed among habitat types and between periods, the most abundant fish species were Atherina sp., Sarpa salpa, Gobiidae, Symphodus spp., Pagellus spp. and several Diplodus species, which colonized 7 up to 14 different habitat types (depending on taxa) during their juvenile life. Most species settled in one or a few specific habitats but rapidly colonized adjacent habitats when growing. This study provided evidence of the role of all types of shallow coastal habitats as fish nurseries and their varying pattern of occupation in space and time by the different juvenile stages. It highlighted the importance of the mosaic of habitats and interfaces for the complete development of all juvenile life stages of fishes, and for the preservation of a high diversity of coastal fish assemblages and fisheries resources in the Mediterranean Sea.